Unraveling relevant factors for effective on farm demonstration: the crucial role of relevance for participants and structural set up. Issue 5 (20th October 2021) - Alexopoulos, Y.; Pappa, E.; Perifanos, I.; Marchand, F.; Cooreman, H.; Debruyne, L.; Chiswell, H.; Ingram, J.; Koutsouris, A.
ABSTRACT: Purpose: The paper focuses on exploring the influence of structural and functional characteristics of demonstrations on their effectiveness. Design/Methodology: In the framework of AgriDemo-F2F project, we analysed the responses to 345 post-demonstration questionnaires filled out by the attendees of 31 demo events held in 12 EU countries. Factor analysis was employed and on a subsequent step a linear regression to predict general effectiveness. Findings: Results indicate that the very first steps in the organisation of on-farm demonstration are of critical importance for the successful delivery of their objectives, particularly decisions relating to relevance to farmers' needs and the structure of the event. Moreover, the paper offers first evidence that when/if on-farm demonstrations are appropriately structured and delivered they can meet their objectives regardless of the status and strength of the corresponding AKIS. Practical implications: Demonstration organisers should take special care with regard to the relevance of the topic and the group (demonstrator and attendees) as well as of the structure of the event. Theoretical implications: The various elements influencing the success of on-farm demonstrations are examined together and ranked. Originality/Value: The study generates important (theoretical and practical) insights concerning the success of a widely used technique of advisory/extension services, that is on-farm demonstrations, based on a large data-set from demonstration events through out Europe.